Supersymmetric solutions of minimal gauged supergravity in five dimensions - Gauntlett,JP; Gutowski,JB (PHYSICAL REVIEW D, 2003)
All purely bosonic supersymmetric solutions of minimal gauged supergravity in five dimensions are classified. The solutions fall into two classes depending on whether the Killing vector constructed from the Killing spinor is timelike or null. When it is timelike, the solutions are determined by a four-dimensional Kähler base manifold, up to an antiholomorphic function, are necessarily not static, and generically preserve 1/2 of the supersymmetry. When it is null we provide a precise prescription for constructing the solutions and we show that they generically preserve 1/4 of the supersymmetry. We show that five-dimensional anti-de Sitter space (AdS5) is the unique maximally supersymmetric configuration. The formalism is used to construct some new solutions, including a nonsingular deformation of AdS5, which can be uplifted to obtain new solutions of type IIB supergravity.